Anti-motilities and anti-biofilm effects of Ageratum conyzoides L. methanol extract - Eli Compaoré; Moussa Compaoré; Vincent Ouédraogo; Ablassé Rouamba; Alimata Bancé; Mignini R. Dofini; Martin Kiendrebeogo (Journal of Medicinal Plants for Economic Development)
Background: Infectious diseases are one of the leading causes of death worldwide because of antibiotic resistance. Ageratum conyzoides is one of the antimicrobial medicinal plants that is being used to fight various multi-resistant pathogenic bacteria in Burkina Faso.